Different robotic structures aiming to help in testing neuroprosthesis control strategies - Poboroniuc, Marian (Ventil (Ljubljana), 2009)
This paper presents some robotic structures and software components aiming to emulate human body motion, while a neuroprosthesis is supposed to provide certain control over the muscles of a disabled person during a rehabilitation process. A Simulink&Matlab model implements the human body model while certain muscles are electrically stimulated and the resulted motion of the human body is shown by controlling a humanoid-like robotic structure. The mainfeature of the proposed humanoid-like robotic structures is support for the training, development, implementation and testing of user defined control algorithms for a neuroprosthesis.
Keywords: biomehanika; električna stimulacija; mehatronika; paraplegiki; robotski mehanizmi